Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Stabilization of dispersive soil by iron ore tailings: A sustainable solution combining waste valorization and geotechnical enhancement - Yuhui Wu; Xiaoqing Yuan; Huicheng Fu; Sen Lin; Xin Xu; Yuxuan Zhou; Xiaoqiang Wang (Minerals Engineering, 2026)

Plant 3D-2D-ResNet-SE: Monitoring the changes of leaf water content and chlorophyll in Betula luminifera seedlings during drought stress - Hao Liang; Shuai Ma; Xiange Hu; Nan Wang; Haoqi Liu; Yuhui Weng; Erpei Lin; Huahong Huang; Xiongwei Lou (Computers and Electronics in Agriculture, 2026)

Curvature and Slope Control on Turbidity Currents and Sedimentation in Submarine Channels: A Numerical Study - Xinhao Wen; Yuechuan Han; Rui Zhu; Enxian Liu; Xiyan Lin; Yuchen Zhang; Yi Zhao; Yuhui Zhang; Jiajun Feng; Dongmei Tian (Journal of Marine Science and Engineering, 2026)
Submarine channels are critical conduits for sediment transport by turbidity currents, yet the quantitative influence of channel geometry on flow dynamics and sediment segregation remains poorly understood. Based on computational fluid dynamics, we constructed six three-dimensional numerical models of submarine channels with varying curvatures (R1–R3) and axial slopes (R4–R6) using ANSYS Fluent 17.2, with model settings informed by seafloor morphology from the South China Sea. The Eulerian–Eulerian multiphase model coupled with the standard k-ε turbulence model was used to simulate density fields, velocity structures, and sediment distributions. Results show that low-curvature channels exhibit symmetric density evolution and uniform sediment distribution, whereas high curvature induces pronounced asymmetry with a steep outer-bank density front and triggers secondary flow reversal. Increasing curvature also enhances flow thickness and radial mass flux. Increasing axial slope markedly elevates downstream velocity (0.09 to 0.16 m/s), reduces flow thickness, and shifts sediment distribution toward the inner bank without inducing secondary flow reversal. This study provides a parametric comparison of curvature versus slope effects on turbidity current dynamics and sedimentation patterns under fixed-bed, rectangular-channel assumptions. The findings offer a qualitative reference for interpreting sedimentary architectures in deep-water systems such as those in the South China Sea and analogous rift basins. Results are hypothesis-generating, pending further validation with field data and morphodynamic modeling.

Durability analysis of using MICP to address dispersive soil issues in seasonal freezing areas - Xiaoqing Yuan; Yuhui Wu; Cencen Niu; Xiaolong Yang; Sen Lin; Zeju Wu; Qing Wang; Hui’e Chen; Xin Xu; Hua Du (Soil and Tillage Research, 2026)

Cenozoic out-of-sequence structural expansion across the northern Tibetan Plateau margin: Insights from differential exhumation of the Altyn Shan and basin deformation - Shibao Gao; Xiaogan Cheng; Xiubin Lin; Baotian Pan; Yuhui Ye; Lei Wu; Kaixuan An; Hanlin Chen; Shufeng Yang (Tectonophysics, 2025)

O-GlcNAc as ammonia-induced glycosylation during the development of hyperammonemia - Hongmei Li; Yuhui Zhao; Zhaoyang Sun; Zeyu Zhao; Siyu Hou; Tao Lin; Tangfei Chen; Jianglong Wu; Qinghong Chen; Chen Zhang; Zheng Li; Jiajun Yang (Journal of Molecular Histology, 2025)

Key odorants driving aroma transformation during aging process in Liubao tea: A sensory and chemical perspective - Ying Yang; Ruijin Qiu; Qiushuang You; Wanjun Ma; Yuhui Zhang; Yan Zhao; Gaozhong Yang; Yue Zhang; Zhi Lin; Yin Zhu; Haipeng Lv (Food Chemistry, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

Thermal runaway dynamics of LFP batteries in confined pressurized atmospheres: From triggering to gas evolution - Lin Yu; Yuhui Wang; Qing Wang; Kuo Wang; Jianqi Zhang; Xinming Qian (Chemical Engineering Journal, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Mechanisms of toxic metal(loid) migration in the slag-soil-groundwater continuum: Geochemical evidence from an abandoned industrial complex - Peng Zhao; Haili Zhang; Xuefeng Yang; Haiyan Wang; Muhammad Adnan; Yunlong Wu; Yuhui Liu; Lin Guo; Hai-Bo Qin; Baohua Xiao; Shengguo Xue (Journal of Cleaner Production, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

A Facile Way to Enhance the Therapeutic Efficacy of Hydrophobic Drugs via Amorphous Solid Dispersions - Ning Tao; Zihui Yan; Xin Wang; Yuhui Wang; Li Ji; Lin Qiu; Pengfei Cui; Jianhao Wang (The AAPS Journal, 2025)

Research on the explosive characteristics and suppression mechanisms of gas generation during thermal runaway of batteries in a charged state - Jianqi Zhang; Fangzhou Li; Lin Yu; Yuhui Wang; Kuo Wang; Chongye Chang; Minghui Li; Wenhao Hao; Xinming Qian (Chemical Engineering Journal, 2025)

Stem cells vesicles-loaded type I pro-photosensitizer for synergetic oxygen-independent phototheranostics and microenvironment regulation in infected diabetic wounds - Qin Zeng; Ying Zhang; Judun Zheng; Jingyan Lin; Ning Li; Minghai Zhao; Xu Chen; Xipeng Li; Meijiao Zhao; Jialin Huang; Qiulin Xie; Ronghua Yang; et al. (Chemical Engineering Journal, 2025)

Transitions between Chinese dynasties influenced by spatial-patterned precipitation - Haowen Fan; Chaoyong Hu; Zunyu Hu; Zherui Lin; Yuhui Liu; Lianlian Li; Rongbei Qin; Jingyun Zheng; Xuejia Wang; Deliang Chen (Quaternary Science Reviews, 2024)

Constraints of multi-source input and coastal transport on the composition of marine clay minerals: A case study of the northwestern shelf of the South China Sea - Yuhui Ai; Anqi Wang; Lin Zhang; Cheng Xu; Xianqing Wang; Shengqiang Yuan; Fangjian Xu (Geo-Marine Letters, 2024)

Large-Scale carbon Fiber-Based Solar-Driven evaporator with 1T MoS2-MXene Heterostructure: Towards reliable mechanical performance and efficient seawater desalination - Lin Jin; Lin Zhang; Hao Liang; Yuhui Ao; Song Wang; De Sun (Chemical Engineering Journal, 2024)

Should local governments adopt dynamic subsidy mechanism to promote the development of green intelligent buildings? An evolutionary game analysis - Yimin Lin; Shuitai Xu; Yuhui Zhou; Lingyan Xiong (Journal of Environmental Management, 2024)

Novel multiphase nano Ni3Bi2S2/NiS anchored on graphite nanosheet for high-capacity sodium-ion battery anodes - Xintong Wang; Dong Feng; Xuezhi Xu; Shandong Huang; Yihong Ding; Jie Lin; Yuhui Xie; Feng Wu; Wenbo Zhao; Tianbiao Zeng; Delong Xie (Chemical Engineering Journal, 2024)

High-performance nonflammable gel polymer electrolyte with 3D interpenetrating network for advanced lithium-ion batteries - Yirou Du; Yuhui Xie; Lin Chen; Fei Hu; Xianshuai Liu; Sihao Yin; Hao Jiang; Xiaodong Liang; Feng Wu; Liang Qiao; Yi Mei; Delong Xie (Chemical Engineering Journal, 2024)

Glaesserella parasuis serotype 5 induces pyroptosis via the RIG-I/MAVS/NLRP3 pathway in swine tracheal epithelial cells - Yuhui Li; Mengru Guo; Qing Wang; Hong Zhou; Wenda Wu; Huixing Lin; Hongjie Fan (Veterinary Microbiology, 2024)

Porcine circovirus type 2 and Glaesserella parasuis serotype 4 co-infection activates Snail1 to disrupt the intercellular junctions and facilitate bacteria translocation across the tracheal epithelium - Mengru Guo; Jianan Zhang; Qing Wang; Jinsheng Tang; Yuhui Li; Hong Zhou; Huixing Lin; Zhe Ma; Hongjie Fan (Veterinary Microbiology, 2024)

Highly ion-conducting, robust and environmentally stable poly(vinyl alcohol) eutectic gels designed by natural polyelectrolytes for flexible wearable sensors and supercapacitors - Bai Huang; Wanwan Liu; Yufan Lan; Yuhui Huang; Lihua Fu; Baofeng Lin; Chuanhui Xu (Chemical Engineering Journal, 2024)

Multiparty distance minimization: Problems and an evolutionary approach - Zeneng She; Wenjian Luo; Xin Lin; Yatong Chang; Yuhui Shi (Swarm and Evolutionary Computation, 2023)

Cover Crops Control Weed and Improve Soil Qualities in Citrus Orchard - Hang Li; Xun Wang; Yuan Li; Yuhui Hou; Ziming Zhao; Lin Meng; Ji Liu; Jun Wang; Bo Xiong; Zhihui Wang (Journal of Soil Science and Plant Nutrition, 2023)

Tidal dynamics regulates potential coupling of carbon‑nitrogen‑sulfur cycling microbes in intertidal flats - Yuhui Niu; Zhirui An; Dengzhou Gao; Feiyang Chen; Jie Zhou; Bolin Liu; Lin Qi; Li Wu; Zhuke Lin; Guoyu Yin; Xia Liang; Hongpo Dong; et al. (Science of The Total Environment, 2023)

3D hierarchical fireproof gel polymer electrolyte towards high-performance and comprehensive safety lithium-ion batteries - Yirou Du; Xianshuai Liu; Lin Chen; Sihao Yin; Yuhui Xie; Ao Li; Xiaodong Liang; Yong Luo; Feng Wu; Yi Mei; Delong Xie (Chemical Engineering Journal, 2023)

Effect of extrusion on the structural and flavor properties of oat flours - Donghao Zhang; Yuhui Zhang; Xin Pan; Lin Yuan; Yanpei Cai; Fei Lao; Jihong Wu (Journal of Cereal Science, 2023)

The reaction pathway and mechanism of 2,4-dichlorophenol removal by modified fly ash-loaded nZVI/Ni particles - Yajun Li; Yongxiang Zhang; Wenjing Yang; Yuhui Lin (Environmental Science and Pollution Research, 2023)

Silver doped-silica nanoparticles reinforced poly (ethylene glycol) diacrylate/hyaluronic acid hydrogel dressings for synergistically accelerating bacterial-infected wound healing - Lin Huang; Wenqiang Li; Mingtao Guo; Zhiguan Huang; Yuhui Chen; Xueping Dong; Yuhe Li; Lin Zhu (Carbohydrate Polymers, 2023)

Effects of periodic drying-wetting on microbial dynamics and activity of nitrite/nitrate-dependent anaerobic methane oxidizers in intertidal wetland sediments - Feiyang Chen; Yuhui Niu; Zhirui An; Li Wu; Jie Zhou; Lin Qi; Guoyu Yin; Hongpo Dong; Xiaofei Li; Dengzhou Gao; Min Liu; Yanling Zheng; et al. (Water Research, 2023)

Transgenic expression of rice OsPHR2 increases phosphorus uptake and yield in wheat - Yan Li; Yuhui Fang; Chaojun Peng; Xia Hua; Yu Zhang; Xueli Qi; Zhengling Li; Yumin Wang; Lin Hu; Weigang Xu (Protoplasma, 2022)

To cheat or to treat? Fungus gnat pollination in Aspidistra - Wei Lin; Yuanqing Xu; Yuhui Jiang; Zhonghui Ma (Ecology, 2022)

Effects of diethyl aminoethyl hexanoate on the physiology and selenium absorption of grape seedlings - Lei Liu; Jiaxi Han; Lili Deng; Huixuan Zhou; Yuhui Bie; Qianhe Jing; Lijin Lin; Jin Wang; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

Effects of mutual grafting Solanum photeinocarpum from two ecosystems on physiology and selenium absorption of their offspring under selenium stress - Kewen Huang; Yan Wang; Xiaohan Wei; Yuhui Bie; Huixuan Zhou; Lili Deng; Lijin Lin; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

Facile Microwave-Assisted Synthesis of Functionalized Carbon Nitride Quantum Dots as Fluorescence Probe for Fast and Highly Selective Detection of 2,4,6-Trinitrophenol - Shikong Lu; Meihua Xue; Aojia Tao; Yuhui Weng; Bixia Yao; Wen Weng; Xiuchun Lin (Journal of Fluorescence, 2021)

Application of Firefly Luciferase (Luc) as a Reporter Gene for the Chemoautotrophic and Acidophilic Acidithiobacillus spp. - Xianke Chen; Xiujie Liu; Yuhui Gao; Jianqiang Lin; Xiangmei Liu; Xin Pang; Jianqun Lin; Linxu Chen (Current Microbiology, 2020)

MiR-615 Regulates NSC Differentiation In Vitro and Contributes to Spinal Cord Injury Repair by Targeting LINGO-1 - Hongfu Wu; Lu Ding; Yuhui Wang; Tang-Bin Zou; Tao Wang; Wenjin Fu; Yong Lin; Xiaomin Zhang; Kangzhen Chen; Yutian Lei; Caitang Zhong; Chuanming Luo (Molecular Neurobiology, 2020)

Stone forest as a small‐scale field model for the study of urban climate - Kai Wang; Yuguo Li; Yuhui Li; Borong Lin (International Journal of Climatology, 2018)
Reduced‐scale physical models of real cities are a useful approach to studying the physical processes of urban climate. Here, we consider a stone forest as a small‐scale field model of urban climate. The study was conducted in the scenic area of stone forest (24.81°N, 103.32°E), located in Yunnan Province in southwest China. The stone forest is a set of limestone formations with heights ranging from 10 to 30 m. These stones are thought to be similar to buildings in cities because the thermal properties of the stones are similar to those of the concrete of human‐made structures in cities. The thermal environment of the stone forest can thus be considered to simulate that of cities. Our field measurements were conducted over 2 years in four different areas to simulate typical urban morphology and environment scenarios, that is, high‐rise compact, low‐rise sparse, garden, and isolated single‐stone areas. The field measurements in the stone forest demonstrated several phenomena common to cities—higher mean temperature, smaller amplitude, and delayed phase lag—as opposed to rural areas. Unlike cities, air pollution and anthropogenic heat are limited in the stone forest; hence, we attribute the differences between the four areas to the effects of stone forest morphology. With increasing compactness, the daily amplitude is reduced and the daily phase delayed. Rather than the mean temperature alone, the daily amplitude and phase may be better indicators of the effects of urban morphology on the daily temperature cycle.

Study of Specific Interaction between bis(p-phenylene)-34-crown-10-based Substituted Macrocycle and Ni2+ - Xin Lin; Yuhui Zheng; Lasheng Jiang; Haoliang Chen; Qianming Wang (Journal of Fluorescence, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Co-altered functional networks and brain structure in unmedicated patients with bipolar and major depressive disorders - Hao He; Jing Sui; Yuhui Du; Qingbao Yu; Dongdong Lin; Wayne C. Drevets; Jonathan B. Savitz; Jian Yang; Teresa A. Victor; Vince D. Calhoun (Brain Structure and Function, 2017)

Erratum to: Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene - Na Qin; Weigang Xu; Lin Hu; Yan Li; Huiwei Wang; Xueli Qi; Yuhui Fang; Xia Hua (Protoplasma, 2016)

Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene - Na Qin; Weigang Xu; Lin Hu; Yan Li; Huiwei Wang; Xueli Qi; Yuhui Fang; Xia Hua (Protoplasma, 2016)

Phosphofructokinase-1 Negatively Regulates Neurogenesis from Neural Stem Cells - Fengyun Zhang; Xiaodan Qian; Cheng Qin; Yuhui Lin; Haiyin Wu; Lei Chang; Chunxia Luo; Dongya Zhu (Neuroscience Bulletin, 2016)

Cadmium exposure and the risk of breast cancer in Chaoshan population of southeast China - Lin Peng; Yiteng Huang; Jingwen Zhang; Yuhui Peng; Xueqiong Lin; Kusheng Wu; Xia Huo (Environmental Science and Pollution Research, 2015)

Expression and Mechanism of BRP-39 in Bleomycin-Induced Pulmonary Fibrosis in Rat - Chunxian Du; Yibing Yang; Yuhui Lin; Jiong Yang (Cell Biochemistry and Biophysics, 2014)